The effects of corporate ownership and board structure on firm performance : evidence from Singapore-listed firms. - Ng, Jia Hui. (2008)
This paper examines the effect of corporate ownership structure and board structure on the performance of Singapore-listed firms. We examine the association between firm performance and board structure. In addition, further analysis was performed by examining the effect of audit, compensation and nominating committees on firm performance.